International Grain Reserves and Other Instruments to Address Volatility in Grain Markets - Wright, Brian D. (Published by Oxford University Press on behalf of the World Bank, 2014)
In the long view, recent volatility of prices of the major grains is not anomalous. Wheat, rice, and maize are highly substitutable in the global market for calories, and when aggregate stocks decline to minimal feasible levels, prices become highly sensitive to small shocks, consistent with the economics of storage behavior. In this decade, stocks declined due to high global income growth and biofuels mandates, making markets unusually sensitive to subsequent unanticipated shocks, including biofuels demand boosts in reaction to high petroleum prices, the Australian drought, and other regional grain production problems. To protect their own vulnerable and politically influential consumers, key exporters restricted supplies in 2007, exacerbating the price rise. Understandably, vulnerable importers are now building strategic reserves. To reduce costs and disincentive effects, reserves should have quantitative goals related to targeted distribution to the most vulnerable in severe emergencies. For countries with significant animal feeding or biofuels industries, options contracts to protect the consumption of the most vulnerable from harvest shocks are likely to be more cost-effective than emergency reserves.